Japan's trade frictions - El - Agraa, Ali M. (London, 1988)
Visiting Japan, one cannot help but notice the overwhelming publicity given to Japan's trade frictions with the USA. Of course, Japan's trade frictions with other nations are mentioned, but the statements made in this regard are completely dwarfed by those made on the trade frictions between Japan and the USA. This bias has also influenced academic analysis: the literature on the US Japan economic problem is expanding while that on, for example, the European Community-Japan problem is almost non existent. Since other nations have also been threatening to undertake, and have occasionally undertaken, drastic measures to curb imports of Japanese products, it seems strange that Japan's trade frictions should be so eschewed towards its bilateral exchanges with the USA. In this book it is argued that Japan's trade frictions cannot be analysed meaningfully except in a global context and within a long-term perspective. After all, Japan has been consistently in trade deficit with the Middle East, a reflection of its dependence on imported energy, and the UK (1800-80), the USA (1915-60) and West Germany (1971-82) ran trade surpluses without causing so much friction.
Keywords: Japan - Economic conditions -1945